Debating emerging adulthood stage or process? - Arnett, Jeffrey Jensen (New York ; Oxford : Oxford University Press, 2011)
Two pairs of developmental psychologists take sides in a debate that is central to the concept of emerging adulthood. They argue that as young people around the world share demographic similarities, such as longer education and later marriage, the years between the ages 18 and 25 are best understood as entailing a new life stage.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: Young adults -- Psychology; Maturation (Psychology); Adulthood